A case series of invasive mucormycosis in patients with COVID-19 infection - Mishra, Neha; Mutya, Venkata Sai Shashank; Thomas, Alphonsa; Rai, Girish; Reddy, Bathi; Mohanan, Anithakumari Alnipully; Ray, Shalina; Thiruvengadem, Anand Vellore; Siddini, Vishwanath; Hegde, Raghuraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Rhino-orbital-cerebral mucormycosis is an invasive disease associated with high mortality ranging from 25-62%. There is an increase in the incidence of mucormycosis in post COVID-19 infection patients. We have come across 10 such patients. On retrospective analysis of the patient’s records, we found that 60% patients had received steroids and majority had co-morbidities. All the patients received similar treatment with IV amphotericin B and local debridement and the mortality rate was as high as 44%. We conclude that patients with COVID 19 infection are susceptible to mucormycosis because of impairment of barrier defense, dysfunction phagocytes and lymphocytes and the use of immunosuppressive medications such as steroids and tocilizumab.